The Relationship Between Entrepreneurship Skills Among UTHM Students And The Importance Of Entrepreneurship Course For Students - Azizan, Anim Zalina; Nur Emylia Natasha, (Research in Management of Technology and Business, 2023)
Entrepreneurship is one of the sectors that help grow a country's economy. One way to achieve so is to provide proper and good education to polish entrepreneurship skills, especially among younger generations. So it can be said that providing education on entrepreneurship can build and improve new skills that indirectly help the country's development. Therefore there is a need for a country to have a firm base of entrepreneurship. This study aims to determine the level of entrepreneurship skills that UTHM students have, the level of importance of entrepreneurship courses and the relationship between entrepreneurship skills of UTHM students and the matter of entrepreneurship courses for students. The method used in collecting data for this study is quantitative. A set of questionnaires was distributed to 283 University Tun Hussein Onn Malaysia students in their 2nd, 3rd and 4th year of the program. This study's key is finding if entrepreneurship courses play a role in students' entrepreneurship skills.